Transient voltage distribution in inverter fed motor windings experimental study and modeling. - Bidan, P. (IEEE Transactions on power electronics)
The different voltage waveforms along with their distribution in the inverter fed motor windings are presented with the help of a specially equipped machine. As a matter of fact, even though a lot has been said on the possible premature failure of such machines, little is known on the internal voltages appearing in the windings or for that matter from a theoretical point of view, the reasons for such voltage distributions. The aim of this paper is to demonstrate that a far more accurate picture emerges by taking into account the energy losses in the iron frame. The use of a new mathematical tool called ?diffusive representation? permits a simple model to be obtained for time-domain simulations. Such an approach gives very good results as demonstrated in the paper